Cholinergic signaling modulates astrocytic D-serine release - Tolman, Michaela. (2018)
Abstract: Cholinergic signaling controls brain states, modulates circuit function, and is a primary therapeutic strategy for a number of diseases including schizophrenia and Alzheimer's disease. Recent work from our lab has demonstrated in mouse hippocampal slices that wakefulness-dependent acetylcholine (ACh) release acts on alpha 7 nicotinic acetylcholine receptors (α7nAChRs) expressed by astrocytes to control the availability of the obligatory NMDA receptor (NMDAR) co-agonist, D-serine. However, cholinergic dependent changes in hippocampal D-serine levels have not been measured in vivo. To do this, I established both high pressure liquid chromatography (HPLC) and microdialysis techniques. Using these two techniques, I found that the level of D-serine detected correlates with the wakefulness state of the mouse, that the α7nAChRs on astrocytes are necessary for maintaining normal hippocampal D-serine levels, social interaction, learning, and memory behaviors in male mice. Ongoing experiments expand our mechanistic understanding of cholinergic signaling by comparing the astrocyte α7nAChR conditional knock-out (cKO) mice to neuronal α7nAChR cKO mice.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Neuroscience.; Advisor: Phil Haydon.; Committee: Thomas Biederer, and Rob Jackson.; Keyword: Neurosciences.